2016
DOI: 10.4102/jamba.v8i3.239
|View full text |Cite
|
Sign up to set email alerts
|

Communal farming, climate change adaptation and the media in Zimbabwe

Abstract: Climate change is destroying Zimbabwean communal farmers’ agricultural activities – a source of living for most people. As communal farmers struggle to adapt, the media is expected to assume a fundamental theoretical role of educating and informing them about the appropriate adaptation techniques. Located in Umguza District in Matabeleland North Province, the study explored how communal farmers created meaning out of climate change media content and its influence on their agricultural practices from October 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…A study in Zimbabwe found that despite widespread access to phones, people were more likely to rely on radio for climate information than for other topics, where mobile phones were more common. 32 In the absence of time or resources to conduct a channel mapping exercise, existing data may provide an indication of channel preferences. For example, a systematic review published in 2020 on communication needs for weather and climate services in sub-Saharan Africa found that farmers showed a strong preference for radio and that communication channel preferences were broadly consistent across different farming groups.…”
Section: Communication Channelsmentioning
confidence: 99%
“…A study in Zimbabwe found that despite widespread access to phones, people were more likely to rely on radio for climate information than for other topics, where mobile phones were more common. 32 In the absence of time or resources to conduct a channel mapping exercise, existing data may provide an indication of channel preferences. For example, a systematic review published in 2020 on communication needs for weather and climate services in sub-Saharan Africa found that farmers showed a strong preference for radio and that communication channel preferences were broadly consistent across different farming groups.…”
Section: Communication Channelsmentioning
confidence: 99%
“…Increased carrying capacity can be achieved through simple techniques like planting pastures, adding fertilizers, and planting additional palatable species. Furthermore Ndhlovu and Mpofu [27] mentioned that conservation agriculture (CA), popularly known as "Farming the God's Way", is one of the most popular climate change adaptation techniques in one of the districts in Zimbabwe. The system is also being introduced in South Africa by land care programs that aim to teach communities to responsibly manage the land by conserving vegetation, water, and biological diversity in their area [28].…”
Section: Water and Land Pollutionmentioning
confidence: 99%
“…Changes in the long-term weather patterns caused by natural or external forces – attributed directly or indirectly – define what is meant by climate change (IPCC 2001a ). Zimbabwe has documented scientific evidence indicating experiences in extreme and adverse effects of climate change (Ndhlovu & Mpofu 2016 ). Adverse weather conditions include severe dry spells, cyclones, heat waves and flooding events.…”
Section: Review Of Related Literaturementioning
confidence: 99%